What about intraspecific variation? Reassessment of taxonomic and phylogenetic characters in the genus Synoeca de Saussure (Hymenoptera: Vespidae: Polistinae) - Cely, Christian C.; Sarmiento, Carlos E. (Zootaxa, 2011)
Morphological variation within and between species of the genus Synoeca was studied to test species status and to propose characters that fulfill the principles of communicability, unit delimitation, and conjunction for taxonomic and phylogenetic analyses. Twenty-six morphological characters obtained from the literature were analyzed; 16 of these characters clearly exhibited delimited states but only four of them were unique for each species. The status of every species of the genus was supported by geometric morphometrics of the head (front view, dorsal view and metasomal tergum 1) and by the presence of unique character states for each species. Phylogenetic analyses included nest and genitalia characters. Character reassessment provided a less resolved tree to that previously published. Including polymorphic characters did not improve tree resolution or clade support, while applying the conjunction test offered a more resolved and better supported tree. The study revealed the importance of analyzing variation in taxonomic and phylogenetic studies within and between species. A new key to species and a phylogenetic hypothesis are offered.